2004
DOI: 10.1136/vr.155.8.225
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural analysis of the efficacy of treatments for injuries to the spinal cord in animals

Abstract: There have been very few clinical trials evaluating therapies for naturally occurring spinal cord injury in dogs and cats. This review describes the methods suitable for evaluating the behavioural recovery of animals with spinal cord injuries, in either a clinical or a laboratory setting. A list of commonly used methods for evaluating behavioural recovery in animals is provided, both in the clinical and laboratory setting; the tests, their limitations and benefits and specific recommendations for their use are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 71 publications
2
13
0
1
Order By: Relevance
“…Olby et al modified the BBB open field scoring system for dogs based on the pelvic limbs [24]. Several investigators have confirmed the reliability of the Olby scoring system [23,38]. The spinal cord injury model in the present study had more than 75% of the spinal canal occluded during a 12 h period; the resulting lesions showed histopathologically severe hemorrhage and vacuolar formation.…”
Section: Discussionsupporting
confidence: 57%
“…Olby et al modified the BBB open field scoring system for dogs based on the pelvic limbs [24]. Several investigators have confirmed the reliability of the Olby scoring system [23,38]. The spinal cord injury model in the present study had more than 75% of the spinal canal occluded during a 12 h period; the resulting lesions showed histopathologically severe hemorrhage and vacuolar formation.…”
Section: Discussionsupporting
confidence: 57%
“…Using a 15-point scoring system (Olby score), the dogs' gaits were independently scored from videotapes by 2 separate individuals who were blinded to the experimental conditions [37]. Mean scores at 1, 3, 5 and 9 weeks after SCI were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Behavioral recovery was scored according to the Olby scoring system [26], which is composed of 15 different criteria. The Olby scoring system is the modified scoring system for dogs based on pelvic limbs, and confirmed the reliability by several investigators [10,24,25]. The gaits of dogs were recorded using video camera, and two different investigators scored the gait.…”
Section: Behavioral Analysis Based On the Olby Scorementioning
confidence: 99%